A Facile and General Oxidative Hydroxylation of Organoboron Compounds: Citric Acid as an Efficient Catalyst in Water to Access Phenolic and Alcoholic Motifs - Jia-Hui Zhou; Xia Chen; Dan Yang; Chun-Yan Liu; Xiao-Yu Zhou (Molecules, 2023)
An efficient and convenient method for the synthesis of phenols and aliphatic alcohols is described in this paper. The oxidative hydroxylation reaction of various organoboron compounds proceeded smoothly by employing H2O2 as the oxidant and citric acid as the catalyst in water at room temperature to produce phenols and aliphatic alcohols in satisfactory to excellent yields (up to 99% yield). Various synthetically useful functional groups, such as halogen atom, cyano, and nitro groups, remain intact during the oxidative hydroxylation. The developed catalytic system also could accommodate phenylboronic pinacol ester and potassium phenyltrifluoroborate to give the target product good yields.